Optocoupler Sensor Optimization for an Arduino Nano–Based Ocean Current Velocity Measurement System - Ahmad Syah Masud Baihaqi; Achmad Solichan; Laily Muntasiroh (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
This study aims to optimize the use of an optocoupler sensor in an Arduino Nano–based ocean current velocity measurement device that is simple, cost-effective, and sufficiently accurate. The measurement system employs a propeller mechanism driven by ocean currents, where the optocoupler sensor detects rotational pulses and the Arduino Nano processes the data to calculate current velocity. The research methodology includes hardware design, software development, and performance evaluation. A comparative testing method was conducted by comparing the measurement results of the developed device with those obtained from a standard ocean current measurement instrument as a reference. Initial test results indicated measurement deviations with an average error of 13.54%, influenced by technical factors such as sensor orientation relative to flow direction, water depth, current turbulence, and data acquisition delay.